1992
DOI: 10.1159/000284748
|View full text |Cite
|
Sign up to set email alerts
|

Age at Onset, Precipitating Events, Sex Distribution, and Co-Occurrence of Anxiety Disorders

Abstract: 178 outpatients were administered to a structured interview evaluating diagnostic, illness history, and sociodemographic data of DSM-III-R anxiety disorders. Patients with panic disorder with agoraphobia were a more severely ill subgroup than patients with panic disorder without agoraphobia. Simple and social phobia had the earliest age at onset, panic disorder the latest age at onset. Conjugal stress was the most frequent event preceding the onset of the anxiety disorders. Female patients showed more severe i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 36 publications
2
11
0
1
Order By: Relevance
“…Prior to the 1994 DSM revision the same criteria were also listed in the child section of the manual under Overanxious Disorder (OAD). Along with specific phobias, GAD/OAD is the most commonly diagnosed anxiety disorder in non-referred youth under 18 years of age (Meltzer et al 1999;Scheibe and Albus 1992). GAD/OAD is also among the most commonly occurring comorbid conditions in youth seeking treatment for separation anxiety, social phobia, panic and obsessive compulsive disorders (Kendall et al 2010;Last et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the 1994 DSM revision the same criteria were also listed in the child section of the manual under Overanxious Disorder (OAD). Along with specific phobias, GAD/OAD is the most commonly diagnosed anxiety disorder in non-referred youth under 18 years of age (Meltzer et al 1999;Scheibe and Albus 1992). GAD/OAD is also among the most commonly occurring comorbid conditions in youth seeking treatment for separation anxiety, social phobia, panic and obsessive compulsive disorders (Kendall et al 2010;Last et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Similar gender differences in epidemiological parameters have also been found within OCD (Grabe et al, 2000; Grant et al, 2010; Kolada et al, 1994; Mohammadi et al, 2004), PD (Eaton et al, 1994; Krystal et al, 1992), GAD (Hunt et al, 2002; Vesga-López et al, 2008) and SAD (Beesdo et al, 2007). In addition, several studies have documented gender differences among clinical samples of individuals with anxiety disorders (e.g., all anxiety disorders: Scheibe & Albus, 1992; Yonkers et al, 2003, PD: Clayton et al, 2006; OCD: Bogetto et al, 1999; Torresan et al, 2009, SAD: Turk et al, 1998; Yonkers et al, 2003). …”
mentioning
confidence: 99%
“…animal), social, and agoraphobic subtypes. This view was supported by Scheibe and Albus [7], who showed that there were differences between the phobia subtypes in the age of onset. The difference between neurotic depression and anxiety neurosis was also emphasized in terms o f comorbidity [8], symptomatology [9, for review see 10], and early life experiences [11].…”
Section: Introductionmentioning
confidence: 78%